2/9y-4=2/3

2/9y-4=2/3 is equal to: y=21
Solution:
Solve for y:
(2 y)/9-4 = 2/3
Put the fractions in (2 y)/9-4 over a common denominator.
Put each term in (2 y)/9-4 over the common denominator 9: (2 y)/9-4 = (2 y)/9-(36)/9:
(2 y)/9-(36)/9 = 2/3
Combine (2 [ y)/9-(36)/9 into a single fraction.
(2 y)/9-(36)/9 = (2 y-36)/9:
(2 y-36)/9 = 2/3
Factor the polynomial, 2 y-36.
Factor 2 from the polynomial 2 y-36:
2 (y-18)/9 = 2/3
Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 (y-18))/9 = 2/3 by 9/2:
((9×2 (y-18))/(2))/(9) = 9/2×2/3
Express 9/2×2/3 as a single

fraction.
9/2×2/3 = (9×2)/(2×3):
(9×2 (y-18))/(2×9) = (9×2)/(2×3)
Cancel common terms in the numerator and denominator of (9×2 (y-18))/(2×9).
(9×2 (y-18))/(2×9) = (2×9)/(2×9)×(y-18) = y-18:
y-18 = (9×2)/(2×3)
Cancel common terms in the numerator and denominator of (9×2)/(2×3).
(9×2)/(2×3) = 2/2×9/3 = 9/3:
y-18 = 9/3
Reduce 9/3 to lowest terms.
The gcd of 9 and 3 is 3, so 9/3 = (3×3)/(3×1) = 3/3×3 = 3:
y-18 = 3
Isolate terms with y to the left hand side.
Add 18 to both sides:
y+(18-18) = 3+18
Look for two terms that sum to zero.
18-18 = 0:
y = 3+18
Evaluate 3+18.
3+18 = 21:
Answer: |
| y = 21
]

Expert answered|emdjay23|Points 2314|

Question

Asked 9/16/2013 2:12:17 PM

Updated 7/31/2014 11:44:35 AM

1 Answer/Comment

Rating

3

2/9y - 4 = 2/3;

2/9y = 2/3 + 4;

2/9y = 14/3;

y = (14/3)/(2/9);

y = (14*9)/(3*2);

y = 126/6;

y = 21

2/9y = 2/3 + 4;

2/9y = 14/3;

y = (14/3)/(2/9);

y = (14*9)/(3*2);

y = 126/6;

y = 21

Added 7/31/2014 11:44:35 AM

This answer has been confirmed as correct and helpful.

1/2y-7=9 **Weegy:** 1/2y-7=9 is equal to: y=32
Solution:
Solve for y:
y/2-7 = 9
Put the fractions in y/2-7 over a common denominator.
Put each term in y/2-7 over the common denominator 2: y/2-7 = y/2-(14)/2:
y/2-(14)/2 = 9
Combine y/2-(14)/2 into a single [ fraction.
y/2-(14)/2 = (y-14)/2:
(y-14)/2 = 9
Multiply both sides by a constant to simplify the equation.
Multiply both sides of (y-14)/2 = 9 by 2:
(2 (y-14))/2 = 2×9
Cancel common terms in the numerator and denominator of (2 (y-14))/2.
(2 (y-14))/2 = 2/2×(y-14) = y-14:
y-14 = 2×9
Multiply 2 and 9 together.
2×9 = 18:
y-14 = 18
Isolate terms with y to the left hand side.
Add 14 to both sides:
y+(14-14) = 18+14
Look for two terms that sum to zero.
14-14 = 0:
y = 18+14
Evaluate 18+14.
18+14 = 32:
Answer: |
| y = 32
] (More)

Question

Expert Answered

Updated 7/28/2014 2:42:10 PM

1 Answer/Comment

1/2y - 7 = 9;

1/2y = 9 + 7;

1/2y = 16;

y = 16/(1/2);

y = 32

1/2y = 9 + 7;

1/2y = 16;

y = 16/(1/2);

y = 32

Added 7/28/2014 2:42:10 PM

This answer has been confirmed as correct and helpful.

27,099,159

questions answered

There are no comments.